The Socioeconomic Impact of Schooling in a Developing Country - Behrman, Jere R.; Wolfe, Barbara L. (The Review of Economics and Statistics, 1984)
tional attainments suggests the usefulness of special training programs for unskilled immigrants. Further, the persistence of racial differentials underscores the importance of the enforcement of anti-bias employment regulations to protect non-white immigrants. Recent changes in immigration law under the Refugee Act of 1980 will increase uncertainty regarding the composition of future immigration waves. It is likely, however, that the proportion of immigrants for whom specialized training and anti-bias regulation enforcement can hasten the traditional catch-up process which has historically characterized the immigrant economic experience will continually increase. Additional research using more recent data will allow both the efficacy of the recommendations advanced and the persistence of the observed patterns to be tested.